Global Trends in Orthodox and Traditional Treatment of Selected Infectious and Non-infectious Diseases - Longo, Emily; McShaffrey, Connor; Alexander, Alexis; Brooks, Rayya; Burke, Kathryn; Padrick, Clare; Kim, Yura; Ayeni, Funmilola (Global Trends in Orthodox and Traditional Treatment of Selected Infectious and Non-infectious Diseases, 2021)
There is an age long conflict in the choice of treatment for several diseased state, to use orthodox or traditional medicine. The choice of the right medical treatment is globally influence by religion, economic consideration, cultural influence and trust. Various global locations develop the traditional medicine treatment that works for them gradually over the years. The widespread use of traditional medicine by communities around the globe emphasizes its importance and the need for constant reports on prevailing global traditional treatment of a variety of endemic conditions. This book therefore explores traditional medicine treatment in various parts of the world for selected infectious (malaria, tuberculosis, cholera) and non-infectious (cancer, infertility, hypertension) diseases.